2022
DOI: 10.1007/s11306-022-01949-w
|View full text |Cite
|
Sign up to set email alerts
|

The metabolomics of a protein kinase C delta (PKCδ) knock-out mouse model

Abstract: Introduction PKCδ is ubiquitously expressed in mammalian cells and its dysregulation plays a key role in the onset of several incurable diseases and metabolic disorders. However, much remains unknown about the metabolic pathways and disturbances induced by PKC deficiency, as well as the metabolic mechanisms involved. Objectives This study aims to use metabolomics to further characterize the function of PKC from a metabolomics standpoint, by comparing the full serum metabolic profiles of PKC deficient mice to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…reported that enzymes required for glycolysis were decreased, while enzymes that regulate lipid biosynthesis were increased in hearts from PKCδ −/− mice ( 18 ). Similarly, loss of PKCδ correlated with a reduction in glycolytic metabolites and an increase in fatty acid metabolites in serum from PKCδ −/− mice ( 19 ). In hepatocytes, PKCδ has been linked to suppression of insulin signaling, activation of NADPH oxidase, and a concomitant increase of oxidative stress ( 20 ).…”
Section: Discussionmentioning
confidence: 97%
“…reported that enzymes required for glycolysis were decreased, while enzymes that regulate lipid biosynthesis were increased in hearts from PKCδ −/− mice ( 18 ). Similarly, loss of PKCδ correlated with a reduction in glycolytic metabolites and an increase in fatty acid metabolites in serum from PKCδ −/− mice ( 19 ). In hepatocytes, PKCδ has been linked to suppression of insulin signaling, activation of NADPH oxidase, and a concomitant increase of oxidative stress ( 20 ).…”
Section: Discussionmentioning
confidence: 97%
“…There are some studies that have contributed to the elucidation of the function of PKCδ in glucose metabolism, under non-tumor conditions. In fact, in a recent work, data from metabolomic analysis demonstrated an inhibition of glycolysis and tricarboxylic acid cycle (TCA), which was associated with an upregulation of other metabolic pathways in PKCδ-deficient mice [ 42 ]. Additionally, regarding mitochondrial respiration, it was described that PKCδ is implicated in the stimulation of the pyruvate dehydrogenase complex activity, thereby increasing the flux of fuel entering the TCA cycle by converting pyruvate to acetyl CoA in the mitochondrial matrix [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%